202 Surfactant and Inhaled Nitric Oxide for Severe Respiratory Distress Complicated with Persistent Pulmonary Hypertension Among Infants below 32 Weeks GA. (October 2012) - Adamczak, A; Gajos, S; Mejsak, A; Merritt, TA; Gadzinowski, J; Mazela, J
Abstract : Introduction: RDS can be complicated by PPHN due to intrauterine or postnatal prolonged hypoxia regardless of surfactant replacement therapy (SRT). Use of iNO therapy is not approved for premature infants < 34 weeks, nevertheless in most severe cases of PPHN use of iNO has been reported. Aim: The aim of this study was to analyze outcomes of infants with severe RDS treated with SRT and iNO in comparison to those treated with SRT only. Methods: Medical records from January 2008 till December 2010 from a level III NICU were analyzed. Only infants < 32 weeks ga and treated with SRT for RDS were included in the study divided in two groups: treated with SRT+iNO (PPHN based on SaO2 differences and echocardiography) and SRT only. Data were analyzed according to maternal history: intrauterine infection, PROM, and clinical outcomes: pneumonia, NEC, ROP, BPD, IVH. Results: 309 premature infants < 32 weeks gestation were treated with SRT, with 54(17%) treated with iNO due to PPHN. There were significant higher ratios of intrauterine infection and early pneumonia in SRT+iNO in 2008 and 2009. The neonatal outcomes showed consistent higher incidence of ROP and PVL for the SRT+iNO group in these same years. The BPD rate remained unchanged at 20% and mortality ranged from 18 to 48%. Conclusions: Severe PPHN was likely caused by ineffective SRT due to presence of inflammation and possible surfactant inactivation. Inhaled NO improved oxygenation and decreased signs of PPHN but did not influence rate of BPD.